Provereno - min net . Certified: No Mines - aka Provereno nema mina - Velimirović, Zdravko; Lysenko, Yurii (Lovchenfilm ; Dovzhenko, 1965)
1944, Belgrade has been liberated, the fascist troops have withdrawn, but before leaving thay decided to blow up the city. The people are unaware of the new dangers. The soldiers are searching the city carefully yet deep under the surface, the whole drainage sytem is stuffed with mines. A group of Soviet and Yugoslav soldiers manage to prevent the explosion.